2021
DOI: 10.3390/biologics1030024
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Evaluation of Different Flavonoids from Medicinal Plants for Their Potency against SARS-CoV-2

Abstract: The ongoing pandemic situation of COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) poses a global threat to both the world economy and public health. Therefore, there is an urgent need to discover effective vaccines or drugs to fight against this virus. The flavonoids and their medicinal plant sources have already exhibited various biological effects, including antiviral, anti-inflammatory, antioxidant, etc. This study was designed to evaluate different flavonoids from medicinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 67 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…Based on molecular docking and ADMET analysis, flavonoids, such as cyanidin-3-(p-coumaroyl)-rutinoside-5-glucoside, delphinidin-3-O-beta-D-glucoside 5-O-(6-coumaroyl-beta-D-glucoside), albireo delphine, apigenin 7-(6”-malonylglucoside), and (-) maackiain-3-O-glucosyl-6”-O-malonate were demonstrated as potent inhibitors against the spike protein, 3CLpro, and RdRP of SARS-CoV-2 [ 18 ]. Furthermore, molecular docking and simulation studies on flavonoid-protein complexes, including luteolin-spike protein and mundulinol-spike protein, have been found to demonstrate strong interactions compared to recently used FDA-approved drugs such as favipiravir, hydroxychloroquine, and lopinavir [ 19 ]. Flavonoids, such as dorsilurin E, euchrenone a11, and sanggenol O, were found to inhibit SARS-CoV-2 main protease (M pro ) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on molecular docking and ADMET analysis, flavonoids, such as cyanidin-3-(p-coumaroyl)-rutinoside-5-glucoside, delphinidin-3-O-beta-D-glucoside 5-O-(6-coumaroyl-beta-D-glucoside), albireo delphine, apigenin 7-(6”-malonylglucoside), and (-) maackiain-3-O-glucosyl-6”-O-malonate were demonstrated as potent inhibitors against the spike protein, 3CLpro, and RdRP of SARS-CoV-2 [ 18 ]. Furthermore, molecular docking and simulation studies on flavonoid-protein complexes, including luteolin-spike protein and mundulinol-spike protein, have been found to demonstrate strong interactions compared to recently used FDA-approved drugs such as favipiravir, hydroxychloroquine, and lopinavir [ 19 ]. Flavonoids, such as dorsilurin E, euchrenone a11, and sanggenol O, were found to inhibit SARS-CoV-2 main protease (M pro ) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking analysis was performed to interpret the interactive profile of the four isolated compounds from W. coccinea with their target proteins. The widely used popular software packages, including PyRx, PyMoL 2.3, and BIOVA Discovery Studio version 4.5, were utilized during for the in silico study of the isolated compounds from W. coccinea according to the semiflexible procedures described in several studies [36][37][38][39][40][41].…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…In-silico screening followed by molecular docking analyses suggested that the phytochemicals bisdemethoxycurcumin, scutellarin, desmethoxycurcumin, quercetin, myricetin, luteolin and mundulinol could potentially inhibit 3-CL pro as these compounds exhibit low binding energy [ 25 , 73 ]. Another study recommended certain compounds such as catechin, naringenin, kaempferol, glucosides, quercetin, and epicatechin-gallate as potential inhibitors of 3CLpro [ 43 ].…”
Section: Replicase Inhibitorsmentioning
confidence: 99%